Immunopathogenesis in Trypanosoma cruzi infection: a role for suppressed macrophages and apoptotic cells - Vellozo, Natália S.; Matos-Silva, Thayane C.; Lopes, Marcela F. (Frontiers in Immunology, 2023)
During Trypanosoma cruzi infection, macrophages phagocytose parasites and remove apoptotic cells through efferocytosis. While macrophage 1 (M1) produces proinflammatory cytokines and NO and fights infection, M2 macrophages are permissive host cells that express arginase 1 and play a role in tissue repair. The regulation of M1 and M2 phenotypes might either induce or impair macrophagemediated immunity towards parasite control or persistence in chronic Chagas disease. Here, we highlight a key role of macrophage activation in early immune responses to T. cruzi that prevents escalating parasitemia, heart parasitism, and mortality during acute infection. We will discuss the mechanisms of macrophage activation and deactivation, such as T cell cytokines and efferocytosis, and how to improve macrophage-mediated immunity to prevent parasite persistence, inflammation, and the development of chagasic cardiomyopathy. Potential vaccines or therapy must enhance early T cell-macrophage crosstalk and parasite control to restrain the pathogenic outcomes of parasiteinduced inflammation in the heart.